Gender differences in repeated dishonest behavior: Experimental evidence - Subhasish M. Chowdhury; Joo Young Jeon; Chulyoung Kim; Sang-Hyun Kim (Games, 2021)
We investigate gender differences in lying behavior when the opportunity to tell lies is repeated. In specific, we distinguish the situations in which such an opportunity can be planned versus when it comes as a surprise. We utilize data from an existing published research and show that when the opportunity to tell a lie comes as a surprise, then on the first occasion, males lie more than females. However, when telling lies can be planned, then there is no gender difference in telling a lie. When planning is possible, females tell more lies in the first occasion compared to when it is not possible to plan; males do not show such behavior. On the second and final occasion, males tell more lies than females when they either could not plan but had the opportunity to a lie before, or could plan but did not have to tell a lie before. These observations can be interpreted in terms of the gender differences in consistent versus compensatory moral behavior.
Keywords: 330; dishonesty; experiment; gender; lying; pre-planning